2019
DOI: 10.1016/j.ijpharm.2019.118696
|View full text |Cite
|
Sign up to set email alerts
|

Montmorillonite-surfactant hybrid particles for modulating intestinal P-glycoprotein-mediated transport

Abstract: In the small intestine, P-glycoprotein (P-gp) may limit the permeability of its substrates, which lead to reduced oral absorption. To circumvent the effect of P-gp, a nanocomposite material termed montmorillonite-surfactant hybrid particles was developed. The particles consisted of montmorillonite, the P-gp-inhibiting, nonionic surfactant, polysorbate 20, and the P-gp substrate, digoxin. The present study aimed to investigate if montmorillonite-surfactant hybrid particles could modulate the absorption of digox… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
4
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 12 publications
(4 citation statements)
references
References 39 publications
0
4
0
Order By: Relevance
“…Naturally, both etoposide and zosuquidar needed to be at the same location at the same time for zosuquidar to elicit an effect on etoposide absorption. Recently, we showed that oral absorption of the P-gp substrate, digoxin, was increased when a P-gp-inhibiting surfactant and digoxin were adsorbed together on a carrier material ( Nielsen et al, 2019 ). Digoxin absorption was likely enhanced by the co-release of substrate and inhibitor, which resulted in a more even distribution.…”
Section: Resultsmentioning
confidence: 99%
“…Naturally, both etoposide and zosuquidar needed to be at the same location at the same time for zosuquidar to elicit an effect on etoposide absorption. Recently, we showed that oral absorption of the P-gp substrate, digoxin, was increased when a P-gp-inhibiting surfactant and digoxin were adsorbed together on a carrier material ( Nielsen et al, 2019 ). Digoxin absorption was likely enhanced by the co-release of substrate and inhibitor, which resulted in a more even distribution.…”
Section: Resultsmentioning
confidence: 99%
“…To inhibit the effect of P-gp, a clay-based nanocomposite using montmorillonite and PS 20 was developed [50]. The particles consisted of montmorillonite, the nonionic surfactant PS 20, and the P-gp substrate digoxin.…”
Section: P-glycoprotein (P-gp) Inhibitory Property Of Psmentioning
confidence: 99%
“…The surfactant (Tween 80 ® ) and the C20A were mixed in a 1:1 (w w À1 ) ratio, 49 and then distilled water was added to the mixture and subjected to high-intensity ultrasound for 10 min, at 1-min intervals and subsequent magnetic stirring for 30 min. After the magnetic stirring, the mixture can be called a dip coating solution.…”
Section: Dip Coatingmentioning
confidence: 99%